2022
DOI: 10.3389/fneur.2022.982630
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted topological properties of the structural brain network in patients with cerebellar infarction on different sides are associated with cognitive impairment

Abstract: PurposeTo explore changes in the brain structural network in patients with cerebellar infarction on different sides and their correlations with changes in cognitive function.MethodsNineteen patients with acute left posterior cerebellar infarction and 18 patients with acute right posterior cerebellar infarction seen from July 2016 to September 2019 in the Department of Neurology, Affiliated Brain Hospital of Nanjing Medical University, were selected. A total of 27 healthy controls matched for sex, age, and year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The study revealed that patients with cerebellar damage exhibited impairments in the allocation of spatio-temporal attention (Craig et al, 2021). In a similar vein, Wang et al (2021) enrolled 36 patients with posterior cerebellar infarction and 30 healthy volunteers for cognitive neurofunctional assessment and MRI scans to extract parameters related to the structural topological features of brain networks. The findings of this study indicated reduced global and local efficiency of brain networks, along with increased clustering coefficients and shortest path lengths within the patient group.…”
Section: Cerebellum and Attentional Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study revealed that patients with cerebellar damage exhibited impairments in the allocation of spatio-temporal attention (Craig et al, 2021). In a similar vein, Wang et al (2021) enrolled 36 patients with posterior cerebellar infarction and 30 healthy volunteers for cognitive neurofunctional assessment and MRI scans to extract parameters related to the structural topological features of brain networks. The findings of this study indicated reduced global and local efficiency of brain networks, along with increased clustering coefficients and shortest path lengths within the patient group.…”
Section: Cerebellum and Attentional Functionmentioning
confidence: 97%
“…The findings of this study indicated reduced global and local efficiency of brain networks, along with increased clustering coefficients and shortest path lengths within the patient group. The authors attributed the observed attentional dysfunction in the cerebellar infarction group to diminished connectivity efficiency within the cerebellar and default networks, as well as the frontotemporoparietal network (Wang et al, 2021). Furthermore, Mannarelli investigated changes in the amplitude of the P3b wave, which is indicative of alterations in attentional function, at various time points in a patient with left posterior lobe cerebellar infarction.…”
Section: Cerebellum and Attentional Functionmentioning
confidence: 99%
“…The known connectivity of the cerebellum with contralateral cerebral regions necessarily raises the question of whether damage to the left or right side of the cerebellum might result in deficits in attention/spatial processing or language (respectively). Although there is a good deal of evidence that language functions are more lateralized to the right cerebellum (for reviews see Marien & Borgatti, 2018;Stoodley & Stein, 2011), the role of the left cerebellum in attention and spatial functions is less established (e.g., Allen, Buxton, Wong, & Courchesne, 1997;Baier, Dieterich, Stoeter, Birklein, & Muller, 2010;Oliver Baumann & Mattingley, 2014;Brissenden, Levin, Osher, Halko, & Somers, 2016;Brissenden & Somers, 2019;Craig, Morrill, Anderson, Danckert, & Striemer, 2021;Gottwald, Mihajlovic, Wilde, & Mehdorn, 2003;Gottwald, Wilde, Mihajlovic, & Mehdorn, 2004;Molinari, Petrosini, Misciagna, & Leggio, 2004;Schweizer, Alexander, Cusimano, & Stuss, 2007;Starowicz-Filip et al, 2021;Striemer, Cantelmi, Cusimano, Danckert, & Schweizer, 2015;Striemer, Chouinard, Goodale, & de Ribaupierre, 2015;Wang, Yao, Lin, Hu, & Shi, 2022).…”
Section: Introductionmentioning
confidence: 99%